Exploration on How Integration Degree into Sport APPs Affect Users’ Attitude and Behavioural Habit towards Physical Exercise - Bo Feng (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
Sport applications (Apps) exert significant influence on users' attitudes and behavioural patterns by virtue of their convenience, accessibility, social engagement, and goal-setting features. This study aims to explore the impact of sports Apps on users' attitudes and behaviours towards sports. Questionnaires were administered, and statistical analyses were conducted, gathering 273 responses. K-test and T-test methodologies were employed. Participants, users of sports Apps, were surveyed to examine how their integration into the virtual communities within these Apps affects their attitudes and behavioural habits towards sports. Findings indicate that the extent of integration into sports Apps significantly correlates with users' attitudes towards physical exercise and their behavioural habits. Deeper integration corresponds with increased activity levels and the establishment of more robust exercise routines across various dimensions. The study suggests that developers should enhance the content of sports and fitness Apps continuously, improving their scientific accuracy. Furthermore, active individuals engaging in physical exercise are encouraged to utilize sports and fitness Apps fully, leveraging their functionalities to enrich their fitness pursuits and cultivate a positive attitude towards sports.